Assessing the Impact of Sustainability-Driven Product Quality and Brand Awareness on Consumer Purchase Decision - Surjono, Welly; Saepudin, Saepudin; Aprianti, Ine; Dewi, Resta Mustika (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This article explores and analyzes the impact of product quality influenced by sustainability and brand understanding on consumer purchasing decisions. Methodology/approach–The research methodology involved designing and testing a questionnaire measuring three main variables: sustainability-influenced product quality, brand understanding, and purchase decision. Data was collected through an online survey processed using descriptive analysis, correlation coefficient, F-test, and t-test hypothesis testing. The population in this study is the population of Bandung City in 2023 as many as 2,506,600 (BPS Bandung City 2024 data), using the Slovin formula sampling technique, a margin of error of 10% was obtained from a sample of 97 respondentsFindings – The results showed that sustainability-driven product quality had a strong relationship with consumer purchasing decisions, while brand understanding had a stronger relationship. Simultaneous analysis indicated that both variables significantly influenced purchase decisions, with brand understanding having a greater impact than product quality Novelty/value – Previous research has extensively explored the individual impacts of product quality and brand awareness on consumer behavior, yet the combined effect of these factors within the context of sustainability remains underexamined.